2011
DOI: 10.1590/s0102-695x2011005000146
|View full text |Cite
|
Sign up to set email alerts
|

Herbs of interest to the Brazilian Federal Government: female reproductive and developmental toxicity studies

Abstract: Abstract:In 2009 the Brazilian Ministry of Health published a document named RENISUS that lists 71 herbs traditionally used in Brazil that could result in phytomedicines to be dispensed by the governmental health care program. This manuscript reviews female reproductive and/or developmental toxicity information of these herbs. More than half (35) of the herbs lack information regarding female reproductive and/or developmental effects. From the fourteen herbs used traditionally to disturb female reproduction, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
4
0
4
Order By: Relevance
“…Because of this, some patients use affordable and cost effective alternative therapy for management of diabetes in the form of traditional medicines, which are both locally available and cheap 2, 4 . Several herbal remedies used in the management of diabetes have been reported to possess hypoglycemic effects [6][7][8][9][10][11] . Among these is Momordica charantia L Fam.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, some patients use affordable and cost effective alternative therapy for management of diabetes in the form of traditional medicines, which are both locally available and cheap 2, 4 . Several herbal remedies used in the management of diabetes have been reported to possess hypoglycemic effects [6][7][8][9][10][11] . Among these is Momordica charantia L Fam.…”
Section: Introductionmentioning
confidence: 99%
“…The most common medicinal use of M. charantia is as an effective treatment of diabetes. Number of studies have been conducted to determine the safety profile of M. charantia in experimental animals; and all have found that M. charantia did not show any kind of toxicity when tested in non-pregnant animals [8, 5156].…”
Section: Discussionmentioning
confidence: 99%
“…As observed for many HMP used by the population, information regarding the safety of P. incarnata use during pregnancy and/or lactation is sparse (Veríssimo et al, 2011). To the best of our knowledge, only one study suggested, in vitro, an uterotonic action of this plant (Ruggy, Smith, 1940).…”
Section: Introductionmentioning
confidence: 99%